Morphological characteristics of the genus Ptilodon (Lepidoptera, Notodontidae) larvae with keys to the species - Dolinskaya, I. V. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2025)
The morphological characters of each larval instar of three Palaearctic notodontid moth species belonging to the genus Ptilodon Hübner, 1822, were examined using a scanning electron microscope and digital microphotography. The shape, colour, pattern and chaetotaxy of the head and body; the microsculpture of the head, and the forms and diversity of the setae, stemmata and mouthparts were examined. A comparative morphological analysis of all these structures is provided. The morphological characteristics during larval development and their transformations are discussed. A key to the three species of the genus Ptilodon from the Palaearctic Region is presented. As a result of the comparative morphological analysis, we identified diagnostic and taxonomic characters for the genus Ptilodon and the studied species. The common characters of some taxa within the family are identified.